Clinical Supervision to Improve the Performance of Elementary Teachers in Generation Alpha - Hestiningtyas, Widya; Nurzafira, Istiqomah; Rosidin, UU; Hariri, Hasan; Sowiyah, Sowiyah (Economic Education and Entrepreneurship Journal, 2023)
The purpose of this study was to describe the application of clinical supervision at the elementary school stage in Lampung Province. This research focuses on combining innovate approaches to clinical supervision with a focus on improving the performance of elementary school teachers in facing the unique challenges of Generation Alpha. The research was conducted in three areas of Lampung Province, namely elementary schools in Bandar Lampung City, Metro City and South Lampung Regency. The research was conducted with a qualitative approach. Sources of research data are school principals and teachers. Data collection techniques use interviews, observation, and documentation techniques. The results of research related to the problems experienced by elementary school teachers are the teacher's lack of interest in using learning media, students' disinterest in learning media, and the teacher's lack of mastery of technology, information, and communication (TIK). Provision of solutions by supervisors, namely in the form of skills training to develop teacher learning media, communicate learning media plans, and learning training based on TIK.Keywords: Clinical Supervision; pedagogic abilities; Elementary School (SD) Teacher; Generation Alpha.DOI: http://dx.doi.org/10.23960/E3J/v6i2.133-138